2018
DOI: 10.1155/2018/3150965
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Mortality in Patients with Nosocomial Acinetobacter baumannii Bacteremia in Southwest China: A Five-Year Case-Control Study

Abstract: Purpose This study was aimed to identify the determinants of in-hospital mortality in Acinetobacter baumannii (A. baumannii) bacteremia and to assess impact of carbapenem resistance on mortality. Methods A five-year case-control study was conducted from January 2011 to December 2015 in a tertiary teaching hospital with 3200 beds, Southwest China. Clinical outcomes and potential determinants of mortality in patients with nosocomial A. baumannii bacteremia and carbapenem-resistant A. baumannii (CRAB) bacteremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…A study conducted in China found a crude and 30-day in-hospital mortality rate of MDR A. baumannii bacteremia of 21.2% and 12.7% respectively, lower than other reports in which high mortality rates ranged from 29% to 63.5%. This difference needs to be clarified as the severity of diseases and virulence factors are closely related to mortality [27]. A previous study carried out in Mexico reported 14.5% mortality [28]; this study included susceptible and resistant A. baumannii strains in a tertiary care teaching hospital; 22% of patients were not hospitalized in the ICU, which reflects less ill patients compared with this series.…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation
“…A study conducted in China found a crude and 30-day in-hospital mortality rate of MDR A. baumannii bacteremia of 21.2% and 12.7% respectively, lower than other reports in which high mortality rates ranged from 29% to 63.5%. This difference needs to be clarified as the severity of diseases and virulence factors are closely related to mortality [27]. A previous study carried out in Mexico reported 14.5% mortality [28]; this study included susceptible and resistant A. baumannii strains in a tertiary care teaching hospital; 22% of patients were not hospitalized in the ICU, which reflects less ill patients compared with this series.…”
Section: Plos Onementioning
confidence: 87%
“…As expected, the difference in mortality was significant when we compared colonized patients (20%) with infected patients (68.2%). Renal failure and SOFA score >7 have been documented as independent risk factors for mortality in the ICU [27,30]. We did not find differences in 30-day mortality when SOFA scores were analyzed at ICU admission, but we found differences when this score was calculated the day when culture was obtained (SOFA �10 was calculated in 30.2% of patients who died in the first month, compared with 9.4% who were alive in the same period of time, p = 0.02).…”
Section: Plos Onementioning
confidence: 99%
“…Bloodstream infections (BSI) caused by CRAB have become a critical public-health threat because CRAB BSI are often associated with worsened outcomes and high risks of morbidity and mortality [5]. However, it remains inconclusive whether carbapenem-resistance status is independently associated with poor outcomes [7–12]. This is a critical question as it will greatly enhance our appreciation on the clinical practice in managing CRAB BSI.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of infections due to MDR Acinetobacter baumannii in Southeast Asia were higher compared to other areas [8,9] , According to a ve-year case-control study from Southwest China, it was the severity of illness (high APACHE II score and MODS) that highlighted the mortality of patients with nosocomial Acinetobacter baumannii bacteremia [10] . The problems for pediatrician in China are polymyxins cannot be obtained, tigecycline only became available in late 2016, and had limited experience in manage these young patients [11,12] .…”
Section: Introductionmentioning
confidence: 99%